2017
DOI: 10.3390/nano7060122
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Structure, Preparation, and Application of NLCs, PNPs, and PLNs

Abstract: Nanostructured lipid carriers (NLCs) are modified solid lipid nanoparticles (SLNs) that retain the characteristics of the SLN, improve drug stability and loading capacity, and prevent drug leakage. Polymer nanoparticles (PNPs) are an important component of drug delivery. These nanoparticles can effectively direct drug delivery to specific targets and improve drug stability and controlled drug release. Lipid–polymer nanoparticles (PLNs), a new type of carrier that combines liposomes and polymers, have been empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(127 citation statements)
references
References 107 publications
0
108
0
5
Order By: Relevance
“…A previous study demonstrated that the incorporation of cholesterol and DOPE into liposomes of the saturated lipid hydrogenated soybean phosphatidylcholine (HSPC) at the appropriate ratio, changed the lipid packing and fluidity of the phospholipid bilayer, resulting in improvements in the entrapment efficiency and stability of genistein-containing liposomes as compared to HSPC liposomes (Phan et al, 2013). HSPC and cholesterol have also been used in the preparation of erlotinibloaded nanocarriers (Li et al, 2017;Mandal et al, 2016). However, the coincorporation of erlotinib and genistein into liposomes has not previously been reported.…”
Section: Entrapment Efficiency Of Erlotinib and Genistein In Liposomesmentioning
confidence: 99%
“…A previous study demonstrated that the incorporation of cholesterol and DOPE into liposomes of the saturated lipid hydrogenated soybean phosphatidylcholine (HSPC) at the appropriate ratio, changed the lipid packing and fluidity of the phospholipid bilayer, resulting in improvements in the entrapment efficiency and stability of genistein-containing liposomes as compared to HSPC liposomes (Phan et al, 2013). HSPC and cholesterol have also been used in the preparation of erlotinibloaded nanocarriers (Li et al, 2017;Mandal et al, 2016). However, the coincorporation of erlotinib and genistein into liposomes has not previously been reported.…”
Section: Entrapment Efficiency Of Erlotinib and Genistein In Liposomesmentioning
confidence: 99%
“…The two components together help inhibit water infiltration and slow hydrolysis down, and as a result prevent drug diffusion and burst leakage. Lipid shell also enhances biocompatibility of nanoparticle with similarity to cell membrane [160]; this is promising in achieving simultaneous co-delivery of multiple drugs [151,152,160]. On the other hand, polymeric core can facilitate mechanical stability, shape control, and size distribution.…”
Section: Lipid-polymer Hybrid Carriers Of Local Anestheticmentioning
confidence: 99%
“…103 One of the drawback of administering immunoliposomes via oral route is that Abs are easily susceptible to destruction by acidic pH of the stomach and enzymes present. 104 Also, the bilayer present in liposome gets digested by bile salts and enzymes if it has no additional protective covering. 105 The penetrative power through mucosa helps liposome to be used effectively in treating inflammation of intestinal mucosal tissue in case of IBD.…”
Section: Nanodrug Delivery System Based On Sizementioning
confidence: 99%